The prolonged observation clarifies the diagnosis of lymphangioma. - Milano, A. (European Journal of Pediatric Dermatology, 2013)
The term lymphangioma designates a malformation of lymphatic vessels, which are not in connection with the normal lymphatic network. We distinguish circumscribed or diffuse lymphangioma, according to the minor or greater delimitation of the lesion, even if the border between the two lesions is not clear (1, 2). Circumscribed lymphangioma is characterized by vesicles reminiscent of frog eggs, sometimes with hemorrhagic content, even if you do not understand the origin of the bleeding. In diffuse lymphangioma edema is often present due to dilatation of deep lymphatic vessels or overflowed lymph. Cystic hygroma is characterized by the presence of a few large lymphatic lacunae. The present case highlights how difficult is the distinction between diffuse and circumscribed lymphangioma and how difficult is even with the help of the MRI the distinc-tion from angiomatous lesions, in the absence of the frog eggs typical appearance. In the oral cavity the tongue is more frequently affected than lips.